2020
DOI: 10.3389/fpls.2019.01588
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pollen Viability for Wheat

Abstract: Wheat sheds tricellular short-lived pollen at maturity. The identification of viable pollen required for high seed set is important for breeders and conservators. The present study aims to evaluate and improve pollen viability tests and to identify factors influencing viability of pollen. In fresh wheat pollen, sucrose was the most abundant soluble sugar (90%). Raffinose was present in minor amounts. However, the analyses of pollen tube growth on 112 liquid and 45 solid media revealed that solid medium with 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 61 publications
0
65
0
1
Order By: Relevance
“…Viable pollen is important for species dispersal, fitness, and survival of the next plant generation (Impe et al, 2020). It is also essential for directed plant breeding and, consequently, crop improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Viable pollen is important for species dispersal, fitness, and survival of the next plant generation (Impe et al, 2020). It is also essential for directed plant breeding and, consequently, crop improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, label-free impedance flow cytometry (IFC) was demonstrated as a useful alternative to the above-mentioned techniques for the analysis of microspore development and characterization of pollen viability in different plant species ( Heidmann et al, 2016 ; Heidmann and Di Berardino, 2017 ; Canonge et al, 2020 ; Impe et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…recorded sunlight promoted biotransformation of Ag + into AgNPs by biomolecules from root exudates. Further, we have earlier reported that dehydrogenases promote reduction Ag + to generate AgNPs [9] and pollen possesses dehydrogenases [1][2][3][4][5]16]. It is well known that Ag 0 and Ag 0 NPs are prone to oxidation under aerobic conditions [9][10][11] and accordingly, as evident from PXRD analysis ( Fig 2D) AgNPs generated by pollen through photoreduction are biphasic made of Ag 0 and Ag 2 O.…”
Section: Plos Onementioning
confidence: 75%
“…In this era of uncontainable increase in human population and malnutrition, wheat breeders are playing a pivotal role in increasing productivity and enhancing quality of wheat grains through hybridization and biotechnology programs. Wheat pollen, which are shed at 3-celled stage, are short-lived [1]. Pollen viability plays a crucial role in general plant breeding programs, which a1111111111 a1111111111 a1111111111 a1111111111 a1111111111…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation